"Scissors‐type" closure of the A'nyemaqen Ocean: Geochronological and geochemical constraints of Late Permian–Triassic granitoids in the East Kunlun Orogen. Issue 2 (18th November 2022) - Wang, Fuchun; Zheng, Tao; Qian, Ye; Yu, Xiaofei; Qiao, Jianfeng
Abstract : The East Kunlun Orogen (EKO) is located in the western part of China and has witnessed the Late Permian–Triassic tectonic evolution involving the A'nyemaqen Ocean (a part of the Palaeo‐Tethys Ocean). In this study, geochronology, geochemistry, and Hf isotope analysis of Late Permian–Triassic granitoids were carried out. Zircon U–Pb dating of Dachagou granodiorite and monzogranite in the western part of the EKO (W–EKO) is 233.4 ± 1.1 and 225.8 ± 1.2 Ma, respectively. The Dachagou granodiorite and monzogranite are characterized by low values of 10, 000 Ga/Al ratios (1.75–2.06, 1.42–1.60) similar to those of I‐type granite. The εHf (t) (−2.4 to +0.1, −3.0 to +0.2) indicate that the magma forming these granites was derived from a mafic Mesoproterozoic lower crust. Zircon U–Pb age of Lalingzaohuo quartz diorite is 244.5 ± 2.6 Ma, and its εHf(t) values (−0.7 to +2.5) indicate the origin of crust–mantle mixing. Zircon U–Pb ages for Nagengkangqieer granodiorite and monzogranite in the eastern part of the EKO (E–EKO) are 250.1 ± 2.8 and 238.9 ± 2.2 Ma, respectively. These rocks are also characterized by low 10, 000 Ga/Al ratios (2.37–2.66 and 2.49–2.63) again similar to I‐type granite. The εHf(t) (−3.9 to 0.4, −3.3 to 1.1) indicate that the magma was derived from the crustal materials. As contemporaneous rocks, the Dachagou and Nagengkangqieer granodiorites and the Lalingzaohuo quartz diorites are formed in a subduction environment. However, the Dachagou and Nagengkangqieer monzogranites are formed in a collision environment. Based on this result, the closure time of the W–EKO and E–EKO of the A'nyemaqen Ocean had an age gap of ~15 Ma, hence the closure mode of the A'nyemaqen Ocean should be a "scissor‐type" closure. Abstract : The W–EKO and E–EKO show different closure timings by 15 Ma. Geochronological and geochemical constraints reveal scissors‐type Ocean closure.